Anaemia in Pregnancy: Prevalence, Risk Factors, and Adverse Perinatal Outcomes in Northern Tanzania - Grace Stephen; Melina Mgongo; Tamara Hussein Hashim; Johnson Katanga; Babill Stray-Pedersen; Sia Emmanueli Msuya (Anemia)
Background and Objective. Anaemia in pregnancy is a public health problem in developing countries. This study aimed to determine the prevalence, risk factors, and adverse perinatal outcomes of anaemia among pregnant women in Moshi Municipal, Northern Tanzania. Methods. This was a follow-up study conducted from October 2013 to June 2015. A total of 539 pregnant women were enrolled in this study. Interviews were conducted followed by determination of haemoglobin level. Women were followed up at delivery and at 7 days and 28 days after delivery. Results. A total of 529 women were included in this analysis. Their mean age was 25.8 (SD 5.73). The prevalence of anaemia was 18.0% and 2% had severe anaemia. The clinic of recruitment and low education level of the women were the factors that were independently associated with anaemia during pregnancy. At delivery, there were 10 stillbirths, 16 low birth weight (LBW) newborns, and 2 preterm birth cases. No association was found between anaemia and LBW, preterm birth, or stillbirths. Conclusion. Anaemia in pregnancy was a mild public health problem in the study setting of Northern Tanzania.